The Relationship Between Intelligence and Creativity Within the Threshold Theory Among Gifted Students in Saudi Arabia - Aboud, Yusra Zaki; AlAli, Rommel (Journal of Ecohumanism, 2024)
Threshold theory is an intelligence and creativity theory that proposes that there is a minimum degree of intelligence, or "threshold," required for creativity to occur. Above this point, intelligence ceases to be a key influence in creativity. This study uses the Threshold Theory to investigate the relationship among exceptional gifted, gifted, and promising gifted students’ creativity and intelligence scores. The study included 3843 gifted students (male=2176; female= 1667). Students in grades three through eleven from the Eastern Province of the Kingdom of Saudi Arabia made up the study sample. The Torrance Creative Thinking exam (TTCT) and the MAWHIBA intelligence test were used (MMCAT). Between 2020 and 2023, a period of three years, data were gathered. The Threshold Theory was applied to test the collected data. The results of the study indicated that the IQ = 118 criterion is evaluated and that there is a positive and significant relationship (r = 0.532; p>0.05) between intelligence and creativity. They are not significantly different from the cutoff (r = 0.22; p > 0.05). Based on the suggested liberal criterion, these findings support the threshold theory.